2015
DOI: 10.2514/1.t4151
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity Performance of a Structurally Embedded Oscillating Heat Pipe

Abstract: The oscillating heat pipe is a novel, simply formed, wickless heat pipe that relies on the phase-change-induced motion of a contained working fluid to transport heat between the evaporator (hot end) and condenser (cold end). The improved heat transfer capability, simplicity, and reduced mass of oscillating heat pipes have led to great interest in the oscillating heat pipe. This paper details the terrestrial and microgravity validation of an ultrasonic consolidation manufactured structurally embedded oscillatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Later on, Manzoni et al [18] proposed an advanced lumped numerical code and the predicted results showed a very good agreement with the experimental thermo-physical behavior during the gravity field transition obtained in [16]. Another test of a PHP in microgravity conditions was performed by Taft et al [19] ) are milled and the device is partially filled up with acetone. The authors observed that when the device was horizontally placed, the thermal response in microgravity was similar to that one on ground, in line with the results obtained by Mameli et al [17].…”
mentioning
confidence: 70%
“…Later on, Manzoni et al [18] proposed an advanced lumped numerical code and the predicted results showed a very good agreement with the experimental thermo-physical behavior during the gravity field transition obtained in [16]. Another test of a PHP in microgravity conditions was performed by Taft et al [19] ) are milled and the device is partially filled up with acetone. The authors observed that when the device was horizontally placed, the thermal response in microgravity was similar to that one on ground, in line with the results obtained by Mameli et al [17].…”
mentioning
confidence: 70%
“…Since OHP operation depends on the dominance of surface tension forces for ensuring capillary flow, the magnitude and direction of gravity will, in general, affect OHP thermal performance [13,17,[25][26][27][28][29][30]. For terrestrial gravity environments (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include: heat pipes/loop heat pipes 18 , annealed pyrolytic graphite panels 23 , and relatively new oscillating heat pipe technologies. 24,25 One such technology is the Thermal Control Panel (TCP) developed by Thermal Management Technologies (Figure 8). This technology provides isothermal structural panels and low thermal impedance joints for use in an isothermal S/C structure.…”
Section: B Reduced Temperature Gradientsmentioning
confidence: 99%